Freedom as a social relationship: A sociological interpretation of Amartya Sen’s capability approach - Otano-Jiménez, Guillermo (Iberoamerican Journal of Development Studies, 2015)
The aim of this paper is to analyze, from a sociological viewpoint, the theoretical and methodological challenges posed by Amartya Sen in his textbook Development as Freedom. The concept of freedom, according with Sen, includes what he calls the «opportunity aspect» and the «process aspect» of freedom. My argument is that the human development paradigm has been more focused in exploring the former than the latter, ignoring the relational dimension of human agency. In order to extend the reach of the capability approach in this direction, I propose to accept three complementary premises: 1) that freedom is a social relationship; 2) that the fights for equality are always constrained by power relations; 3) that the agents in these scenarios are collective actors, rather than individuals.